Na jakich podstawach opiera się mechanika klasyczna: odpowiedź historyka nauki - Bailhache, Patrice (Acta Universitatis Lodziensis. Folia Philosophica. Ethica-Aesthetica-Practica, 1995)
The author tries to give an answer to the question posed in the title of the paper by referring to those analyses and arguments which have been found important by the history of science (laws of Stevin, d'Alembert, Lagrange, arguments of Lazure Carnot, Prony, Ampère, Laplace…). In his opinion the only possible philosophy of mechanics must have the empirical nature. The problem was perceived already by Archimedes, though it was later obscured by numerous metaphysics. Yet, it is only solution of Lagrange which can be said to be approaching the ideal. However, the philosophical part of the arguments still remains unsettled.